2006
DOI: 10.1161/circulationaha.105.577577
|View full text |Cite
|
Sign up to set email alerts
|

Hemoglobin Level, Chronic Kidney Disease, and the Risks of Death and Hospitalization in Adults With Chronic Heart Failure

Abstract: Background— Previous studies have associated reduced hemoglobin levels with increased adverse events in heart failure. It is unclear, however, whether this relation is explained by underlying kidney disease, treatment differences, or associated comorbidity. Methods and Results— We examined the associations between hemoglobin level, kidney function, and risks of death and hospitalization in persons with chronic he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
266
3
13

Year Published

2006
2006
2022
2022

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 458 publications
(300 citation statements)
references
References 46 publications
18
266
3
13
Order By: Relevance
“…These results agree with what have previously been shown [3, 4, 17, 18]. In addition however, the analysis presented here indicates that CKD remains an important independent predictor of HRU even after accounting for other comorbidities.…”
Section: Discussionsupporting
confidence: 93%
“…These results agree with what have previously been shown [3, 4, 17, 18]. In addition however, the analysis presented here indicates that CKD remains an important independent predictor of HRU even after accounting for other comorbidities.…”
Section: Discussionsupporting
confidence: 93%
“…Prevalence of left ventricular hypertrophy (LVH) is inversely related to eGFR and approximately 3 of 4 patients with stage 5 CKD have LVH at the time of dialysis initiation [27,28]. Many posit that nontraditional risk factors consequential to CKD such as anemia, hyperphosphatemia, increased fibroblast growth factor-23 levels, inflammation and unmeasured uremic factors account for at least some of the excess cardiovascular risk [2,29,30,31,32,33]. However, to date, no studies have demonstrated that these unique factors improve the classification of CVD risk in adults with CKD above and beyond traditional cardiovascular risk factors.…”
Section: What Factors Account For Excess Cvd Risk Associated With Ckd?mentioning
confidence: 99%
“…For example, Go et al (22) found that reduced (<13 g/dL) hemoglobin levels and chronic kidney disease independently predict substantially increased risks of death and hospitalization in heart failure, regardless of the level of systolic function. Furthermore, they also concluded that randomized trials are required to evaluate whether raising hemoglobin levels can improve outcomes in chronic heart failure.…”
Section: Discussionmentioning
confidence: 99%